USF1/CD90 signaling in maintaining glioblastoma stem cells and tumor-associated macrophages adhesion. Issue 9 (14th March 2022) - Zhou, Yuanshuai; Meng, Xingjun; He, Wen; Li, Xinying; Zhao, Rongchuan; Dong, Caihua; Yuan, Detian; Yang, Jiao; Zhang, Ruobing; Shi, Guohua; Huang, Yulun; Liu, Jiangang; et al.
Abstract: Background: Glioblastoma stem cells (GSCs) and their interplay with tumor-associated macrophages (TAMs) are responsible for malignant growth and tumor recurrence of glioblastoma multiforme (GBM), but the underlying mechanisms are largely unknown. Methods: Cell viability, stemness, migration, and invasion were measured in GSCs after the knockdown of upstream stimulating factor 1 ( USF1 ). Luciferase assay and chromatin immunoprecipitation qPCR were performed to determine the regulation of CD90 by USF1 . Immunohistochemistry and immunofluorescent staining were used to examine the expression of USF1 and GSC markers, as well as the crosstalk between GSCs and TAMs. In addition, the interaction between GSCs and TAMs was confirmed using in vivo GBM models. Results: We show that USF1 promotes malignant glioblastoma phenotypes and GSCs-TAMs physical interaction by inducing CD90 expression. USF1 predicts a poor prognosis for glioma patients and is upregulated in patient-derived GSCs and glioblastoma cell lines. USF1 overexpression increases the proliferation, invasion, and neurosphere formation of GSCs and glioblastoma cell lines, while USF1 knockdown exerts an opposite effect. Further mechanistic studies reveal that USF1 promotes GSC stemness by directly regulating CD90 expression. Importantly, CD90 of GSCs functions as an anchor for physical interaction with macrophages. Additionally, the USF1 / CD90 signaling axis supports the GSCs and TAMs adhesion and immunosuppressive feature of TAMs, which in turn enhance the stemness of GSCs. Moreover, the overexpression of CD90 restores the stemness property in USF1 knockdown GSCs and its immunosuppressive microenvironment. Conclusions: Our findings indicate that the USF1 / CD90 axis might be a potential therapeutic target for the treatment of glioblastoma.